TRADISI MANGKAHINGI’ DI DESA BUANGIN KECAMATAN RANTEBULAHAN TIMUR KABUPATEN MAMASA - Srinovita, Ewis; Ibrahim, Ibrahim; Said, Muh (xxxx-xxxx, 2023)
The purpose of the study is to find out 1). Overview of the implementation of the Mangkahingi' Tradition in Buangin Village, East Rantebulahan District, Mamasa Regency. 2). How are the values contained in the Mangkahingi Tradition in Buangin Village, East Rantebulahan District, Mamasa Regency. 3). How to implement the values of the Mangkahingi Tradition in the lives of the community in Buangin Village, East Rantebulahan District, Mamasa Regency. This type of research is descriptive qualitative. Data analysis techniques used in research are data reduction, data presentation, and conclusion or verification. The results of the study, showed that 1). The description of the implementation of the Mangkahingi Tradition in Buangin Village, East Rantebulahan District, Mamasa Regency has been started decades ago by ancestors who have become a hereditary culture in society. Tradis Mangkahingi' is held twice a year in June and December. The tradition of Mangkahingi' is carried out in the morning. The procession of the implementation of the Mangkahingi' tradition in accordance with the teachings of Christianity includes welcomes, opening prayers, sermons, closing prayers and eating together with the community. 2). The values contained in the Mangkahingi' Tradition in Buangin Village, East Rantebulahan District, Mamasa Regency are religious values, namely the value of gratitude and the value of almsgiving. And social values, namely the value of gotong-royong, the value of friendship and the value of deliberation. 3). The implementation of the values of the Mangkahingi Tradition in the lives of the community in Buangin Village, East Rantebulahan District, Mamasa Regency (a) The value of gratitude is reflected in the community being grateful for the new home and success in education (b) The value of alms is reflected in the community contributing to the sick community (c) The value of mutual assistance is reflected in community service work (d) The value of friendship is reflected in the wedding party of the community greeting each other (e) the value of deliberation It is reflected in the community deciding the results of their deliberations in the form of approval.